An analysis of corporate board networks in South Africa - I. N. Durbach; H. Parker (South African Journal of Business Management, 2009)
In this paper we analyse the networks created from directors sitting on the boards of companies in South Africa. We consider two projections of this network: a director network, in which only directors are present and two directors are linked if they sit together on one or more common boards; and a firm network, in which only firms are present and an edge indicates that the two firms share one or more directors. We describe these networks in terms of the statistical properties that they possess, and compare them to theoretical values obtained under various random network models. The network analysis is the first to be applied to a relatively small emerging economy like South Africa. We find that many of the features previously found to hold for highly-developed countries also apply here, suggesting that corporate networks may be fairly robust to stages of economic development.
Keywords: 650